Comparison of the accuracy of dynamic navigation and the free hand approaches in the placement of pterygoid implants in the completely edentulous maxilla: An in vitro study - Baoxin Tao; Ningtao Wang; Xiaowan Ling; Lijuan Ye; Yiqun Wu (Elsevier, 2024)
Background/purpose: Pterygoid implant is a promising solution for patients with a partially or fully edentulous atrophic maxilla. However, whether dynamic navigation system will improve the accuracy of pterygoid implant surgery is still unknown. This study aimed to compare the accuracy of dynamic navigation and free-hand approaches in pterygoid implant placement in completely edentulous maxilla models. Materials and methods: Twenty three-dimensional (3D)-printed edentulous maxilla models were assigned to two groups: the dynamic navigation system group and the free-hand group. Two pterygoid implants were planned in the bilateral pterygomaxillary area and then placed in each model. The entry, exit and angle deviations of the pterygoid implants were measured after pre- and post-operative cone-beam CT (CBCT) image fusion. Student's t test and Mann-Whitney U test were used. A P value < 0.05 was considered statistically significant. Results: A total of 40 pterygoid implants were placed in 20 models. The comparison deviation of the dynamic navigation group and the free-hand group showed a mean (±SD) entry deviation of 0.93 ± 0.46 mm vs. 2.28 ± 1.08 mm (P < 0.001), an exit deviation of 1.37 ± 0.52 mm vs. 3.14 ± 1.82 mm (P < 0.001), and an angle deviation of 2.41 ± 1.24° vs. 10.13 ± 4.68° (P < 0.001). There was no significant difference in the accuracy with regard to the side factors between the navigation group and the free-hand group. Conclusion: The dynamic navigation system has higher accuracy for pterygoid implant placement in a complete edentulous maxilla than the free-hand approach.